PERKAWINAN BEDA AGAMA DALAM UNDANG-UNDANG PERKAWINAN DAN HAK ASASI MANUSIA - Syahputra, Ali (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. This research is motivated by differences in understanding studying the Marriage Law and Human Rights in interfaith marriages so there is an unfinished debate, this is because religious teachings do not allow interfaith marriages. As we know that in Indonesia many interfaith marriages are practiced in various ways, such as holding weddings abroad, submitting to the religion of one of the partners, court decisions, and marriages under the umbrella of non-governmental organizations. These are the efforts to legalize interfaith marriages. Aim. The refore the author is interested in studying how interfaith marriages are in Marriage Law and Human Rights. Methods. The method used in this research is library research. Regarding reading dissertations and journals that explain interfaith marriages using a descriptive approach. Results. The results of this study are that the Marriage Law and Human Rights in interfaith marriages are interconnected, where Human Rights return to the Marriage Law and the Marriage Law returns to the teachings of their respective religions. Indonesia uses the Margin of Appreciation theory in which each country has the right to determine its laws without having to follow or be based on the Universal Declaration of Human Rights (UHDR). With the existence of a margin of appreciation, each individual has different rights from the national interest.